1990
DOI: 10.1366/0003702904086975
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Polystyrene by Gamma-Radiation

Abstract: The effect of gamma-radiation on the surface chemical properties of polystyrene was studied by ESCA and FT-IR. Gamma-radiation produces surface >C=O and C-O containing functional groups only, and also causes oxidation to depths >10 nm as detected by ESCA. FT-IR spectra showed that below the top few molecular layers ester, acid, and carbonyl groups of various types were present. The α,β-unsaturated carbonyl/acid groups form a higher proportion of the total carbonyls with increasing depth. Surface oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…7a and b. The only noticeable difference between irradiation in vacuum and in oxygen is the presence of a broad absorption band peaking near 1730 cm À1 , which is due to the formation of carbonyl groups (C]O), for the latter environment, similar to that reported for normal PS [34]. Using the styrene aromatic band at 1500 cm À1 as a reference, it can be seen that the intensity of the 1730 cm À1 band increases with increasing dose.…”
Section: Chemical and Morphological Behaviors Of Isothermally Crystalsupporting
confidence: 65%
“…7a and b. The only noticeable difference between irradiation in vacuum and in oxygen is the presence of a broad absorption band peaking near 1730 cm À1 , which is due to the formation of carbonyl groups (C]O), for the latter environment, similar to that reported for normal PS [34]. Using the styrene aromatic band at 1500 cm À1 as a reference, it can be seen that the intensity of the 1730 cm À1 band increases with increasing dose.…”
Section: Chemical and Morphological Behaviors Of Isothermally Crystalsupporting
confidence: 65%
“…In the latter case, the gamma irradiation is known to initiate radical formation and in the presence of air to lead to the incorporation of 10-20% of surface oxygen. The oxidized polystyrene surface contains numerous reactive groups, including ␣, ␤-unsaturated carbonyl groups (41), which likely form adducts with the ␤ 2 GP1 (15,40). In addition, investigators have reported that some aPLs bind to various coagulation factors, such as prothrombin (42), and again it is interesting that in some cases these antibodies may be directed at PL-bound prothrombin (43).…”
Section: Discussionmentioning
confidence: 99%
“…UV irradiation and X-ray irradiation lead to opening of the polystyrene aromatic ring and comparatively much higher oxygen incorporation into the surface. Whereas the corona profile decreases linearly with depth, the UV profile exhibits a dramatic increase with depth and the gamma profile shows a relatively flat oxidation level over [1][2][3][4][5][6][7][8][9][10] nm sampling depth.…”
Section: Discussionmentioning
confidence: 99%